A Strategic Leadership Approach To Conflict Resolution In Papua - Nila Aulia Khairunnisa; Anang Puji Utama; Bayu Setiawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study, titled "Strategic Leadership Approaches in Conflict Resolution in Papua," aims to explore how strategic leadership can contribute to resolving conflicts in Papua. The research focuses on two main areas: the impact of strategic leadership competencies on conflict resolution and the application of strategic leadership guidelines within organizational culture. First, the study examines the influence of strategic leadership competencies on the effectiveness of conflict resolution in Papua. These competencies include the ability to plan, implement, and evaluate strategies, as well as adapt to changing situations. The research evaluates how leaders with strong strategic competencies can facilitate dialogue, build consensus, and design sustainable solutions for long-standing conflicts. Second, the study assesses the application of strategic leadership guidelines within the context of organizational culture. Understanding the local culture and applying leadership principles that align with the organizational culture are central to this analysis. The research investigates how formal procedures and strategic control are used to manage and resolve conflicts effectively within organizations operating in Papua. The findings indicate that effective strategic leadership requires a deep understanding of the local context and skills in designing and implementing adaptive strategies. Integrating cultural values with leadership principles is crucial for building harmonious relationships and resolving conflicts. This research provides practical insights for leaders in designing more inclusive and responsive approaches to conflict resolution in Papua.